The study of free coumarins in the plant raw material of Medicago falcata L. subsp. romanica (Prodan) O. Schwаrz & Klink - Grechana, O. V.; Гречана, Олена Володимирівна; Гречаная, Е. В. (My University, 2014)
The article presents the data of the pharmacognostic research of the plant raw material from the overground parts of Medicago falcata L. subsp. romanica (Prodan) O. Schwarz & Klink. The aim of our work was to determine the composition and the quantitative content of the components from the true coumarins class revealing the anticoagulation effect. The plant raw material was collected in the period of active vegetation. It was dried in a draught at the temperatures up to 40°C. For the first time gas-liquid chromatography with mass spectrometric detection of the raw material extract has been performed. The components have been identified by the library of mass spectra NIST 05 and WILEY 2007 together with the programmes for identifying AMDIS and NIST. The internal standard method has been used for quantitative calculations. The data obtained have shown the presence of 66 compounds, and 38 of them have been identified and quantitatively characterized. The extract from the raw material of Medicago falcata L. subsp. romanica (Prodan) O.Schwarz & Klink contains a number of biologically active substances in the native form – fatty acid and primary products of biosynthesis. Dihydrocoumarin and coumarin in the corresponding amounts have been identified from compounds of the true coumarin class in the overground parts of alfalfa (M. falcata L. subsp. romanica). У роботі наведені дані фармакогностичного вивчення рослинної сировини надземної частини Medicago falcata L. subsp. romanica (Prodan) O. Schwаrz & Klink. Метою роботи вважали визначення та кількісну характеристику компонентів з класу істинних кумаринів, які виявляли антикоагуляційну дію. Заготовляли рослинну сировину в період масової вегетації. Висушували на протязі при температурі до 40°С. Вперше було проведено газо-рідинне хроматографування з мас-спектрометричним детектуванням екстракту з сировини. Компоненти ідентифікували за допомогою бібліотеки мас-спектрів NIST 05 і WILEY 2007 спільно з програмами для ідентифікації AMDIS і NIST. Для кількісних розрахунків використовували метод внутрішнього стандарту. Отримані дані свідчили про наявність 66 сполук, з яких ідентифіковано і кількісно охарактеризовано 38 компонентів. При ідентифікації екстракт із сировини Medicago falcata L. subsp. romanica (Prodan) O. Schwаrz & Klink. в нативному вигляді містив ряд біологічно активних речовин – жирні кислоти і продукти первинного біосинтезу. З класу істинних кумаринів у заготовлених надземних частинах люцерни посівної (син. румунської) було ідентифіковано дигідрокумарин і кумарин у відповідних кількостях. В работе поданы данные фармакогностического изучения растительного сырья надземной части Medicago falcata L. subsp. romanica (Prodan) O. Schwаrz & Klink. Целью работы считали определение и количественную характеристику компонентов из класса истинных кумаринов, которые проявляют антикоагуляционное действие. Заготавливали растительное сырье в период массовой вегетации. Высушивали на сквозняке при температуре до 40°С. Впервые было проведено газо-жидкостное хроматографирование с масс-спектрометрическим детектированием экстракта из сырья. Компоненты идентифицировали с помощью библиотеки масс-спектров NIST 05 и WILEY 2007 совместно с программами для идентификации AMDIS и NIST. Для количественных расчетов использовали метод внутреннего стандарта. Полученные данные свидетельствовали о наличии 66 соединений, из которых идентифицировано и количественно охарактеризовано 38 компонентов. При идентификации экстракт из сырья Medicago falcata L. subsp. romanica (Prodan) O. Schwаrz & Klink. в нативном виде содержал ряд биологически активных веществ – жирные кислоты и продукты первичного биосинтеза. Из класса истинных кумаринов в заготовленных надземных частях люцерны посевной (син. румынской) были идентифицированы дигидрокумарин и кумарин в соответствующих количествах.
Вивчення вільних кумаринів у рослинній сировині medicago falcata l. Subsp. Romanica (prodan) o. Schwаrz & klink.
Изучение свободных кумаринов в растительном сырье medicago falcata l. Subsp. Romanica (prodan) o. Schwаrz & klink.
Keywords: Medicago falcata L. subsp. romanica (Prodan) O. Schwarz & Klink; pharmacognostic research; coumarins; фармакогностичне дослідження; кумарини; фармакогностическое исследование; кумарины